Appraisal of the doctrine of separation of power and its applicability in modern governance for national development in Nigeria (2018)
In every society, especially one that upholds democratic principles, there are usually laid down rules, principles and customs to guide the society referred to as the Constitution. A constitution is the organic law of a nation. It may be written or unwritten. By nature, the primary objective of the constitution is to lay down the basic principles to which an internal life of a country is conformed, organizing the government, regulating, distributing and limiting the functions of its three different principal organs. This paper seeks to examine the doctrine of separation of powers and its applicability in modern governance in Nigeria. The objective of this is to expose its use as instrument of national development. The paper adopts the doctrinal methodology in search for data. It reveals that a fundamental principle underpinning modern governments is that of separation of powers, with a rider that separation of powers can only function properly where there is interplay between it and the principle of checks and balances. The doctrine is presented as a prelude to the conclusion proposed in this paper, which amongst others include that the people who constitute the government should observe the doctrine of separation of powers within the context of the concept of checks and balances as antidote to abuse of power.